Factors Affecting and Affected by Principal Leadership Effectiveness: A Systematic Literature Review - Hardianto, Hardianto; Aida, Welven; Sari, Vivi Puspita (FKIP Universitas Lampung, 2022)
Principal Leadership Effectiveness. Objective: This study aims to determine the effectiveness of the principal's leadership by looking at the urgency of the principal's leadership, the variables that affect the principal's leadership and the variables that are influenced by the principal's leadership. Methods: The research method used is the literature study method. The data obtained were then compiled and concluded based on the research objectives. Findings: The research findings show that the principal's leadership plays a very important role in realizing educational goals. There are three variables that affect the principal's leadership and eight variables that are influenced by the principal's leadership. Conclusion: Recruitment of school principals must be in accordance with the rules and training for existing school principals is necessary. Mastery of the 4C formula must be owned by the principal. Keywords: effectiveness, leadership, principal.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202202